Absenteeism of Malaysian identity in art in the early years of independence - Abdullah, Sarena (2010)
This paper discusses the shaping of modern art identity in Malaysia during the 1950s and 1960s. It frames or investigates the development of modern art in terms of Malaysia’s plural society. While writings by Malaysian art historians such as Redza Piyadasa highlights that Malaysian modern art only in terms of its linear development, this paper attempts to discuss the early development of modern art in Malaysia as being influenced either directly or indirectly by the political and social conditions of Malaysia, therefore shifting ways of investigating Malaysia art in a wider context of Malaysia’s cultural and plural studies. Focusing on Malaysian fine arts in the 1950s and 1960s, this paper suggests the ways that Malaysia’s early form of plural society had influenced the early modern art development among artists in groups such as the Nanyang, Wednesday Art Group (WAG) and Angkatan Pelukis Semenanjung (APS).